Successful thoracoscopic removal of a giant teratoma following extraction of cystic conponents: A case report. Issue 1 (January 2014) - Miyauchi, Yoshihiro; Matsubara, Hirochika; Uchida, Tsuyoshi; Matsuoka, Hiroyasu; Ichihara, Tomofumi; Matsumoto, Masahiko
Abstract Video‐assisted thoracoscopic surgery is a type of minimal‐access surgery. The nature of the surgery means that there are limitations on the size of a tumor that can be removed through an access incision. Herein, we report our experience removing a giant teratoma (16 × 14 × 13 cm in size) from the anterior mediastinum of a young girl. We employed video‐assisted thoracoscopic surgery to remove the teratoma through a mini‐thoracotomy following the extraction of the cystic components.